The Influence of Administering Propolis CMCE Extract on FSH, LH, and Testosterone Levels in MSG-Induced Male Wistar Rat - Sofyanita, Eko Naning; Nasihun, Taufiqurrachman; Zulaikhah, Siti Thomas (Sains Medika: Jurnal Kedokteran dan Kesehatan, 2019)
Introduction: Monosodium Glutamate (MSG) increase free radicals and effecting on male reproductive hormone balance. CMCE propolis extract can be used as supplement to protect cells from free radical.Objective : To prove the effect of CMCE propolis extract to increase FSH, LH and Testosterone levels in male Wistar rats induced by MSG.Methods : This research was an experimental with post test only control group design used 18 male Wistar rats and divided into 3 groups. Each group on Control (K), P1 and P2 were induced by MSG of 140mg, then on P1 added 8,3mg CMCE propolis extract and P2 10,8mg for 21 days. Then on 22th day of blood was taken through the orbitalis sinus and serum was used for the analysis FSH, LH and Testosteron levels with ELISA method.ResultsÂ : ANOVA analysis test showed significant differences each group p=0,000(pË‚0,05). Post hoc LSD test showed FSH, LH and Testosterone levels in the 8,3mg dose CMCE propolis extract and 10,8mg were significant different compared with control group p=0,000(pË‚0,05). CMCE propolis extract 10,8mg dose had the significantly highest effect of FSH, LH and Testosterone levels than CMCE propolis extract 8,3 mg.Conclusion : CMCE propolis extract 10,8mg/day for 21 days is proven to increase FSH, LH and testosterone levels in male Wistar rats induced by MSG.